Ethanol-induced changes in neurotrophic and immune genes are regulated by receptor-type protein tyrosine phosphatase β/ζ (RPTPβ/ζ) and microglial-neuronal interactions - Penedo, María Aránzazu; Cañeque-Rufo, Héctor; Gramage, Esther; Herradón, Gonzalo (Frontiers in Genetics, 2025)
Microglial cells are key mediators of ethanol-induced neuroinflammation through the release of proinflammatory cytokines and activation of Toll-like receptors. Recently, the signaling pathway initiated by the interaction of the neurotrophic factors pleiotrophin (PTN) and midkine (MK) with receptor-type protein tyrosine phosphatase β/ζ (RPTPβ/ζ) has emerged as a pharmacological target in ethanol-induced neuroinflammatory and neurodegenerative processes. However, the underlying molecular mechanisms remain unclear. In this study, we developed a human co-culture system composed of differentiated SH-SY5Y neuronal cells and HMC3 microglial cells to simulate microglial-neuronal interactions during ethanol exposure. In HMC3 cells, PTN mRNA expression levels were significantly upregulated by ethanol exposure, whereas MK levels were not altered. In contrast, ethanol exposure caused a significant downregulation of MK expression in co-cultures. In general, ethanol increased the expression of inflammatory genes in monocultures of HMC3 cells but not in SH-SY5Y cells. In addition, ethanol exposure caused a highly significant upregulation of TLR3 and TLR4 in HMC3 cells, which was absent in co-cultures. We also observed a significant attenuation of ethanol-induced increases of inflammatory markers such as IL-1β and CCL2 in co-cultures, indicating the regulatory role of neuronal-microglial interactions. In conclusion, our study provides novel insights into the modulatory actions of microglial-neuronal interactions in ethanol-induced neuroimmune responses and suggests the therapeutic potential of the PTN/RPTPβ/ζ signaling pathway to prevent the deleterious effects of alcohol on the brain.